2015
DOI: 10.1371/journal.pone.0120762
|View full text |Cite|
|
Sign up to set email alerts
|

Early Parental Loss and Self-Rated Health of Older Women and Men: A Population-Based, Multi-Country Study

Abstract: ObjectiveDeath of a parent in childhood can diminish both the nurturing that promotes healthy development, and household income. We consider, for the first time, whether this adverse childhood experience is associated with self-rated health decades later, among seniors and whether this lifelong effect is different for women and men.MethodsThe International Mobility in Aging (IMIAS) study is a prospective cohort with survey information and biophysical measures and markers from 2000 community-dwelling 65–74 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 25 publications
(26 reference statements)
0
14
2
Order By: Relevance
“…Parental death (10.1%) also had a higher prevalence than in other studies conducted in developed countries, which varied from 2.6% to 7.4% ( Bethell et al, 2014 , Li et al, 2014 , Stikkelbroek et al, 2012 ). However, it was lower than in a multi-country study, which found 17% early parental death (before the age of 16) and 25% in Brazil ( Phillips & Carver, 2015 ), although it was evaluated in a poorer region of Brazil than this study. The prevalence of parental death in middle-income countries is higher than in high-income countries ( Phillips & Carver, 2015 ), and other studies also show that father's death is more common than mother's death ( Li et al, 2012 ).…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Parental death (10.1%) also had a higher prevalence than in other studies conducted in developed countries, which varied from 2.6% to 7.4% ( Bethell et al, 2014 , Li et al, 2014 , Stikkelbroek et al, 2012 ). However, it was lower than in a multi-country study, which found 17% early parental death (before the age of 16) and 25% in Brazil ( Phillips & Carver, 2015 ), although it was evaluated in a poorer region of Brazil than this study. The prevalence of parental death in middle-income countries is higher than in high-income countries ( Phillips & Carver, 2015 ), and other studies also show that father's death is more common than mother's death ( Li et al, 2012 ).…”
Section: Discussioncontrasting
confidence: 88%
“…However, it was lower than in a multi-country study, which found 17% early parental death (before the age of 16) and 25% in Brazil ( Phillips & Carver, 2015 ), although it was evaluated in a poorer region of Brazil than this study. The prevalence of parental death in middle-income countries is higher than in high-income countries ( Phillips & Carver, 2015 ), and other studies also show that father's death is more common than mother's death ( Li et al, 2012 ). The loss of a parent is always a difficult situation to deal with, especially if it occurs early in life.…”
Section: Discussioncontrasting
confidence: 88%
“…It can also aid in confirming the results of molecular genetics analysis. Recently, Loconte et al described three patients with PIK3CA -related overgrowth syndrome, including one patient with MCAP, and demonstrated the usefulness of a combination of genetic and biochemical methods [28]. They used skin fibroblasts for biochemical investigation, partially because some of their patients showed somatic mosaicism involving only limited parts of the limbs.…”
Section: Discussionmentioning
confidence: 99%
“…Prior IMIAS analyses showed early loss of a parent to be a predictor of poorer health for men but not women ( Phillips & Carver, 2015 ). Current findings suggest that this female advantage did not arise from subsequent resilience as there was no association with, nor difference in adult resilience between men and women who experienced early parental loss.…”
Section: Discussionmentioning
confidence: 99%
“…Unanswered questions about what constitutes adversity, the nature of resilience, and social circumstances that foster bouncing back and thriving remain. For example, parental loss in childhood, although rarely included in studies of adverse childhood experiences (ACE) is emerging as a potent and sustained source of adversity ( Luecken and Roubinov, 2012 , Li et al, 2014 , Phillips and Carver, 2015 ). Because resilience is a dynamic attribute.…”
Section: Introductionmentioning
confidence: 99%